The Influence of Coffee Product Quality, Food Product Quality and Price on Consumer Loyalty in Mediation of Customer Satisfaction at Coffeeshop Konnichiwa Pantai Indah Kapuk - Bondan Pambudi; Antonius Rizki Krisnandi; Dhanik Puspita Sari; Anak Agung Gde Agung; Jakaria Jakaria (International Journal Labs, 2024)
Coffee is one of the most popular beverages in the world. It has become a common thing for people in big cities. This has an impact on the existing coffee business. The quality of coffee products affects consumer loyalty. This study aims to study the relationship between price, quality of food products, and consumer satisfaction. The data analysis method used in this study is Partial Least Squares (PLS) using Smart PLS 3.0 software. The structural equation modeling is used to predict construct structural indicators. The results of these calculations show that the structural model has a good goodness of fit value.